Management of external invasive cervical root resorption in mandibular canine using Biodentine as a restorative material: A case report - Eftekhar, Leila; Ashraf, Hengameh; Jabbari, Sanaa (Iranian Endodontic Journal, 2017)
Invasive cervical root resorption (ICR) is (ir) reversible loss of tooth structure in the connective tissue attachment zone. The etiology is not fully understood; in the present case a history of periodontal surgery was presumed to be a predisposing factor. Early diagnosis and proper treatment may lead to long-term retention of the tooth. The tooth is usually asymptomatic and diagnosis is commonly made as a result of a routine radiographic finding and Cone-Beam Computed Tomography (CBCT) is extremely useful in diagnosis and treatment planning of ICR. The treatment should aim toward complete removal of the resorptive defect and reconstruction by placement of a suitable filling material. The aim of this article is to demonstrate management of mandibular canine with invasive cervical root resorption using biodentine for restoring the defect.